Young survivor of a rare primary anaplastic large cell lymphoma of the trachea - Jehanzeb Shahid (SAGE Publishing, 2021)
Primary anaplastic large cell lymphoma of the trachea is a very rare tumor. Diagnosis is often missed for a long time because the presentation often resembles that of obstructive airway disease. A 24-year-old non-smoker male presented at an outpatient clinic complaining of gradual development of stridor and shortness of breath over a recent period of four weeks. Imaging workup revealed a large lobulated, soft tissue, mildly enhancing, eccentrically placed intraluminal proximal tracheal mass, which showed extension outside of the tracheal lumen in the peritracheal fat. The patient underwent surgery. A biopsy of the resected mass reported anaplastic large cell lymphoma. Post-operation, the patient underwent chemotherapy consisting of four cycles of CHOP (cyclophosphamide, doxorubicin, vincristine and prednisolone). Follow-up imaging showed non-visualization of the mass. Primary lymphoma (anaplastic large cell lymphoma, which is a rare type of non-Hodgkin’s lymphoma) of the trachea is a rare tumor. Early curative resection with post-operative chemotherapy has a favorable outcome, as in our case.